Financial Crises and the Composition of Cross-Border Lending - Cerutti, Eugenio (IMF Working Papers; Working Paper, 2014)
We examine the composition and drivers of cross-border bank lending between 1995 and 2012, distinguishing between syndicated and non-syndicated loans. We show that on-balance sheet syndicated loan exposures account for almost one third of total cross-border loan exposures during this period. Furthermore, syndicated loan exposures increased during the global financial crisis due to large drawdowns on credit lines extended before the crisis. Our empirical analysis of the drivers of cross-border loan exposures in a large bilateral dataset shows three main results. First, banks with lower levels of capital favor syndicated over other kinds of cross-border loans. Second, borrower country characteristics such as level of development, economic size, and capital account openness, are less important in driving syndicated than non-syndicated loan activity, suggesting a diversification motive for syndication. Third, information asymmetries between lender and borrower countries, which are important both in normal and crisis times, became more binding for both types of cross-border lending activity during the recent crisis.